(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives The aim of the present study is to discover the relationship between QT dispersion and severity of CAD as detected by SYNTAX score in stable patients who suffered acute MI. Methods The present study includes 50 patients admitted to Al-Azhar Assuit university hospital and Sohag cardiac center by acute MI. Results The patient age group ranged from 49 -70 years with a mean ± SD (58.8 ± 10.1).. 60% were males and 40% were females.. There was no significant difference found between the two studied groups regarding male gender (p-value 0.564). There was no significant difference between the two groups regarding hypertension (p-value 0.774), smoking (p-value 0.569) and dyslipidemia (p-value 0.508). There is no significant difference between the two study groups regarding the troponin (p-value 0.610) and LDL (p-value 0.557).There was no significant difference between the two groups regarding the echocardiographic data (EF p-value 0.243) (RWMA p-value 0.529) . There was highly significant difference between the two group studies regarding the localization of the vessels lesion (p-value ˂0.001). There was highly significant difference between the two study groups regarding the mean of SYNTAX score (p-value˂0.001). Conclusion The study found that patient with prolonged QTc dispersion >60 milliseconds had more severe involvement of the coronary arteries by atherosclerosis compared to patient with QT c dispersion < 60 milliseconds.